An empirical analysis of the economic impact of air pollution - Edward Mateosian (Economics and Econometrics Research Institute (EERI), 2023)
We attempt to record the imprint of air pollution on economic growth and vice versa, the tendency of economic growth on air pollution. The variables examined in our study are the Particulate Matter Lower than 2.5 micro, GDP per capita, GDP per working hour, Unemployment, Part of the budget for the health sector, Expenditures for medical care, Average annual temperature and Average annual precipitation. The databases used are OECD and World Bank and the data consist of OECD countries. After specification tests, the methodology consists of three specifications to produce robust results and to compare them consistently: panel data with fixed, random and pooled OLS, Difference and System GMM estimators, and the augmented mean value (AMG) estimator. The result is ambiguous as in some cases pollution seems to have a positive relationship with economic growth and in other cases their relationship is negative. On the contrary, the economic product always has a positive effect on air pollution.
Keywords: F43; Q52; Q53; 330; Air pollution; economic growth; augmented mean value estimator; panel data